Protein Hydrolysates from Cucumeropsis mannii Seed Inhibit Alpha-amylase In-vitro: Potential for Managing Postprandial Hyperglycemia - Babatunde, Oladimeji Taiwo; Bewaji, Clement Olatunbosun; Igunnu, Adedoyin (Biology, Medicine, & Natural Product Chemistry, 2025)
Diabetes mellitus is a significant global cause of mortality. A hallmark of diabetes pathophysiology is postprandial hyperglycaemia (PPH). PPH is defined as a sudden and exponential increase in blood glucose levels after meals, typically above 140 mg/dL, which does not return to pre-meal levels after two to three hours, leading to glucose toxicity, oxidative stress, cardiovascular risks, and diabetes complications. A management option for PPH is the inhibition of carbohydrate-metabolizing enzymes, such as alpha-amylase. However, current inhibitors are associated with gastrointestinal side effects. Therefore, the search for novel inhibitors is a rational research endeavor. Recent studies highlight plant-derived protein hydrolysates as inhibitors of alpha-amylase. In this study, proteins from Cucumeropsis mannii (C. mannii) were isolated using alkaline solubilization-acid precipitation method and enzymatically cleaved using pepsin and pancreatin to yield C. mannii seed protein hydrolysates. The ?-amylase inhibitory property of the hydrolysates was investigated, using starch as the substrate. The IC50 values for ?-amylase inhibition were 8.77 ± 0.35 mg/mL (pancreatin-derived) and 14.80 ± 0.50 mg/mL (pepsin-derived). Kinetic studies indicated uncompetitive inhibition for pancreatin-derived hydrolysate and mixed uncompetitive for pepsin-derived hydrolysate at 9 mg/mL. These results suggest that C. mannii seed protein hydrolysates may aid in postprandial hyperglycemia management through ?-amylase inhibition.